The Assessment of Thailand’s Investment Protection Regime in Connection with Its Prospective Participation in the Trans-Pacific Partnership Agreement - Techagaisiyavanit, Wanaporn; Torut, Buraskorn (วารสารเศรษฐศาสตร์และนโยบายสาธารณะ, 2016)
Economic opportunities presented by the Trans-Pacific Partnership Agreement (TPP) have drawn Thailand’s interest into gaining its membership since the Yingluck administration back in 2012. Faced with national trade and investment policy challenges, Thailand seems to have fallen into an ambivalent position. This research article aims at analyzing Thailand’s investment protection regime in comparison to the investment protection standards under the TPP’s Investment Chapter, which has set trends for modern day Free Trade Agreements (FTAs). Despite Thailand’s conservative investment protection policy, and its inconsistency with the TPP’s Investment Chapter, the study has shown there are certain approaches which Thai policymakers can consider that can help address policy challenges present in the area of investment protection. This research article will present an insight on Thailand’s investment protection policy, with some technical knowledge. โครงการการศึกษาและวิเคราะห์นโยบายการคุ้มครองการลงทุนของไทยสำหรับเตรียมความพร้อมเพื่อเข้าร่วมความตกลงหุ้นส่วนภาคพื้นแปซิฟิก โอกาสทางเศรษฐกิจซึ่งสะท้อนอยู่ภายใต้ความตกลงหุ้นส่วนทางเศรษฐกิจภาคพื้นแปซิกฟิกได้ทำให้ประเทศไทยแสดงความสนใจที่จะเข้าร่วมเป็นสมาชิกนับตั้งแต่รัฐบาลยิ่งลักษณ์ เมื่อปี ค.ศ. 2012 แต่ความท้าท้ายในนโยบายด้านการค้าการลงทุนกลับทำให้ไทยตกอยู่ในสภาวะลังเล บทความวิจัยชิ้นนี้จึงมีวัตถุประสงค์เพื่อมุ่งวิเคราะห์นโยบายการให้ความคุ้มครองการลงทุนของประเทศไทยเพื่อเปรียบเทียบกับมาตรฐานการคุ้มครองการลงทุนภายใต้บทลงทุนของความตกลงหุ้นส่วนทางเศรษฐกิจภาคพื้นแปซิกฟิก ซึ่งถือเป็นความตกลงการค้าเสรีสำคัญที่มีบทบาทต่อการกำหนดแนวโน้มมาตรฐานด้านการให้ความคุ้มครองการลงทุนของความตกลงการค้าเสรีในปัจจุบัน อย่างไรก็ตาม แม้ประเทศไทยจะมีนโยบายด้านการคุ้มครองการลงทุนในรูปแบบอนุรักษ์นิยมและไม่สอดคล้องกับมาตรฐานของบทลงทุนของความตกลงหุ้นส่วนทางเศรษฐกิจภาคพื้นแปซิกฟิก งานวิจัยได้ชี้ให้เห็นแนวทางเพื่อให้ผู้วางนโยบายสามารถนำไปใช้พิจารณาเพื่อแก้ไขปัญหาความท้าทายด้านนโยบายการให้ความคุ้มครองการลงทุน งานวิจัยชิ้นนี้จะนำเสนอการวิเคราะห์เชิงลึกสำหรับนโยบายด้านการคุ้มครองการลงทุนของประเทศไทยโดยอาศัยความรู้ทางเทคนิค